STUDY OF SATISFACTION: OPEN SPACE HOUSING IN THE SOUTH TANGERANG REGION - Mona Anggiani; Rona Fika Jamila (Universitas Mercu Buana, 2019)
Housing is one of the necessities that must be fulfilled by every human being so that in the procurement of housing, the government has issued its own rules and regulations. Human needs are no less important that related to house is the existence of facilities. One of the essential means that needs to be held on housing is to conduct social activities or interaction among citizens. However, developers as providers of commercial houses in private housing have provided open space is also intended as one place for residents to social activities and did not escape the requirements of reforestation. The problem is what needs to be studied, what the problem is. This research is designed to find out the extent of the successful use of open space that has been provided by developers in private housing. By evaluating open space user satisfaction on house, referring to certain variables both from the non-physical and physical side is the method to be done in this research. The results of the study state that open space in Grand Serpong 2 housing is quite good from accessibility factors. But the less maintained condition of the open space made the residents less interested in visiting the room so that the occupants' attachment to the space was not good enough. Hopefully, if the discovery of the response of housing, residents can be used as one of thought or consideration for the future for housing providers, to provide open space that can be utilized by the citizens.